1987
DOI: 10.4141/cjas87-120
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of the Cyanogenic Glycosides Amygdalin, Prunasin and Linamarin by Ruminal Microorganisms

Abstract: Three cyanogenic glycosides were incubated simultaneously but separately in rumen fluid from cattle to determine the rates of glycoside hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Some researchers reported that heat processing of flaxseed did not change its HCN content 11. This could be due to the fact that the HCN formed after cyanogenic glycoside hydrolysis remain in flax products, or the deactivation of glycosidase in plant tissue could be replaced by the glycosidase formed by gut microflora 18–20. It is reasonable to state that effective flaxseed processing requires more than just cyanogenic glycoside hydrolysis or deactivation of glycosidase in tissue alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that heat processing of flaxseed did not change its HCN content 11. This could be due to the fact that the HCN formed after cyanogenic glycoside hydrolysis remain in flax products, or the deactivation of glycosidase in plant tissue could be replaced by the glycosidase formed by gut microflora 18–20. It is reasonable to state that effective flaxseed processing requires more than just cyanogenic glycoside hydrolysis or deactivation of glycosidase in tissue alone.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse growing conditions like drought can increase the level of cyanide present in plants (Pickrell et aI., 1991). Cyanide is detoxified in ruminants through the formation of thiocyanates produced either in the rumen or after absorption of cyanide from the gastrointestinal tract (Majak and Cheng, 1987;Onwuka et at., 1992;Salkowski and Penney, 1994). In the rumen, rates of cyanogenesis are pH-dependent, with high rates of cyanide production observed when ruminal pH exceeds 6.0 (Majak et at., 1990).…”
Section: Cyanogenic Gtycosidesmentioning
confidence: 99%
“…The high cyanogenic activity of mixed populations of ruminal bacteria (19,20) suggests that this is not an isolated case and that other enzymes with activity towards these cyanogenic compounds are present in the rumen. Preliminary qualitative studies indicate that CdxA is also capable of releasing free cyanide from both prunasin and amygdalin (data not shown).…”
mentioning
confidence: 99%
“…In the 1980s Majak and Cheng (19,20) demonstrated that many ruminal bacteria, including P. ruminicola, have the ability to release free cyanide from the glycosides amygdalin (laetrile), prunasin, and linamarin. ␤-Glucosidases play a key role in the initial step of hydrolyzing these compounds into glucose units and the cyanogenic aglycone (8,22).…”
mentioning
confidence: 99%